Neuroprotective Effect of S-trans, Trans-farnesylthiosalicylic Acid via Inhibition of RAS/ERK Pathway for the Treatment of Alzheimer’s Disease - Wang X; Wang Y; Zhu Y; Yan L; Zhao L (Dove Medical Press, 2019)
Xiang Wang,1 Yu Wang,2 Yiyi Zhu,1 Luxia Yan,1 Liandong Zhao1 1Department of Neurology, Xuzhou Medical University Affiliated Hospital of Huaian, Huai’an, Jiangsu Province 223002, People’s Republic of China; 2Department of Neurology, The Fourth Affiliated Hospital of Nanjing Medical University, Nanjing Pukou Hospital, Nanjing, Jiangsu 210000, People’s Republic of ChinaCorrespondence: Liandong ZhaoDepartment of Neurology, Xuzhou Medical University Affiliated Hospital of Huaian, No 62 Huaihainan Road, Huai’an, Jiangsu Province 223002, People’s Republic of ChinaTel/Fax +86 517 80871724Email zldong@163.comBackground: Alzheimer’s disease (AD), a leading cause of dementia, becomes a serious health issue for individuals and society around the world. AD is a neurodegenerative disease characterized by the deposition of amyloid-β (Aβ) peptides and neurofibrillary tangles (NFT) and the loss of large numbers of neurons. To date, there is no effective treatment for AD, and thus, to enhance neurogenesis in the AD brain may be a therapeutic strategy. RAS signaling pathway involves in synaptic plasticity and memory formation, which is overexpressed in brains with AD. This study used Aβ1-42-injected mice (Aβ1-42-mice) as the AD model to investigate the effects of S-trans, trans-farnesylthiosalicylic acid (FTS), a synthetic Ras inhibitor, on the impairment of neurogenesis and the spatial cognitive deﬁcits.Materials and methods: AD model mice were manufactured through intracerebroventricular injection of Aβ1-42. Morris water maze (MWM) was performed to evaluate the capacity of spatial memory, and Nissl staining was applied to assess neuronal damage in the hippocampus CA1. Immunohistochemistry of 5-bromo-2-deoxyuridine (BrdU), BrdU/neuronal nuclei (NeuN), and doublecortin (DCX) were used to detect progenitor cell proliferation, maturation, and neurite growth, respectively. And the expression levels of RAS, ERK/ERK phosphorylation (p-ERK) and CREB/CREB phosphorylation (p-CREB) were detected by Western blot.Results: The results demonstrated that FTS could prevent Aβ1-42 to impair survival and neurite growth of newborn neurons in the hippocampal dentate gyrus (DG) in Aβ1-42-mice. Furthermore, behavioral indexes and morphological findings showed that FTS improved the learning and spatial memory abilities of Aβ1-42-mice. In addition, FTS could inhibit the levels of hippocampal p-ERK and p-CREB activated by Aβ, which is the underlying molecular mechanism.Conclusion: In conclusion, these findings suggest that FTS as a RAS inhibitor could be a potential therapeutic agent for the treatment of AD.Keywords: Alzheimer’s disease, S-trans, trans-farnesylthiosalicylic acid, spatial cognition, amyloid-β, neurogenesis, signaling pathway